Mental health in postgraduate programs: thoughts and perspectives on mental illness among the students - Fernandes, Márcia Astrês; Ribeiro, Amanda Alves de Alencar (Revista de Enfermagem da UFPI, 2024)
Postgraduate education represents a path of important value in professional training and in the development of remarkable research and studies for the scientific community. For this purpose, postgraduate programs are permanently aiming to provide proper teaching qualification achieved through a joint collective effort made by coordinators, teachers and students, as well as partnerships with other national and international higher education institutions. However, although the paths are generally prosperous, postgraduate programs also bring challenges and difficulties that may turn into obstacles in this experience. Recent research on mental health has highlighted the presence of symptoms related to depression, anxiety, or stress among postgraduate students. Although mental illness among master's and doctoral students is a complex and multifaceted phenomenon, some guiding questions can be highlighted to understand this scenario. The numerous requirements demanded by the course and the intense dedication necessary to construct a research project combined with a multidimensional set of social, individual, economic and/or interpersonal factors have the potential to significantly impact the psycho-emotional balance of postgraduate students and can also be predictive factors for mental distress. Furthermore, the continuous pressure to maintain a significant production of high-quality original research papers in journals of great scientific impact [...]